Machine Translation Tools - Tools of the Translator’s Trade - Kastberg, Peter; Andersson, Thomas Buch (Communication & Language at Work, 2012)
In this article three of the more common types of translation tools are presented, discussed and critically evaluated. The types of translation tools dealt with in this article are: Fully Automated Machine Translation (or FAMT), Human Aided Machine Translation (or HAMT) and Machine Aided Human Translation (or MAHT). The strengths and weaknesses of the different types of tools are discussed and evaluated by means of a number of examples. The article aims at two things: at presenting a sort of state of the art of what is commonly referred to as “machine translation” as well as at providing the reader with a sound basis for considering what translation tool (if any) is the most appropriate in order to meet his or her specific translation needs. (Translated by Thomas Buch Andersson)